Risk-reducing Salpingo-oophorectomy consults and practices during the COVID-19 pandemic - A.E. O'Mara; C. Benedict; A.W. Kurian; S.K. Wagner; E. Diver (Elsevier, 2022)
Objective: Investigate the impact of the COVID-19 pandemic on risk-reducing salpingo-oophorectomies (RRSO) consults. Methods: Survey sent out to 1,127 full members of the Society of Gynecologic Oncology in August 2021. Survey data included physician characteristics, practice location, and self-reported subjective and objective data about their RRSO consults. Results: We received 70 responses; half of the respondents were female; the mean age of respondents was 46 (range 35-65). 86% of providers transitioned RRSO consults to telehealth. There was no correlation between uptake of telemedicine by age (R2 = 0.09) or gender (p = 0.80), but there was increased use in the West Coast region (p < 0.01). There was a small decrease in average time spent discussing sexual function over telehealth (35 s). Most providers felt comfortable discussing sexual health and function via telehealth. Conclusions: Overall, telemedicine is now commonly used for RRSO consults and physicians noted very few barriers to its uptake. Discussion of sexual function was similar between modalities, the loss of the pelvic exam or private setting did not affect the time providers spent discussing sexual health, however sexual health topics discussed were limited.